2018
DOI: 10.5204/rep.eprints.123533
|View full text |Cite
|
Sign up to set email alerts
|

Strategic review of Cape York Income management

Abstract: BasicsCard A pin-protected key card that can be used with standard EFTPOS facilities to enable access to income-managed money. The BasicsCard can only be used at merchants approved by the Department of Human Services. Breach or breach notification A notification received by the FRC that a client has breached an agreed social obligation trigger outlined in the Family Responsibilities Commission Act 2008 (Qld) ('FRC Act'). Notifications can be received for school attendance (s40), school enrolment (s41), child s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…For example the FRC adopts an ‘enablement’ approach insofar as its Local Commissioners, when conferencing individuals who have been triggered to attend the Commission, seek to increase capabilities and opportunities by listening, advising and referring clients to a range of social services. There is also an element of ‘coercion’ and ‘restriction’ insofar as the FRC is also able to impose income management where it deems it necessary (usually in about 10% of cases; Scott, Higginson, Staines, Zhen, & Ryan, ). Income management places restrictions on individual spending behaviours, removing the individual's ability to spend their welfare‐derived income on certain items (e.g.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example the FRC adopts an ‘enablement’ approach insofar as its Local Commissioners, when conferencing individuals who have been triggered to attend the Commission, seek to increase capabilities and opportunities by listening, advising and referring clients to a range of social services. There is also an element of ‘coercion’ and ‘restriction’ insofar as the FRC is also able to impose income management where it deems it necessary (usually in about 10% of cases; Scott, Higginson, Staines, Zhen, & Ryan, ). Income management places restrictions on individual spending behaviours, removing the individual's ability to spend their welfare‐derived income on certain items (e.g.…”
Section: Resultsmentioning
confidence: 99%
“…Higginson, Staines, Zhen, & Ryan, 2018). Income management places restrictions on individual spending behaviours, removing the individual's ability to spend their welfare-derived income on certain items (e.g.…”
Section: Nature Of Programmatic Theories Of Change and Behavioural-chmentioning
confidence: 99%
“…Thus, the scheme there is relatively young and Doomadgee was not one of the communities involved in the original consultation around the scheme. CYIM also operates differently there (Scott et al., 2018).…”
Section: Methodsmentioning
confidence: 99%
“…This paper examines these nuances in relation to CYWR and CYIM. In particular, we discuss key qualitative findings from a strategic review of CYIM, funded by the Federal Government and completed in late 2018 (Scott et al., 2018). The review involved a mixed‐methods approach, including analyses of 10 years of data from the FRC and thematic analysis of qualitative data, including policy documentation, reports, and a small number of interviews with members of the FRC.…”
Section: Introductionmentioning
confidence: 99%
“…He concluded that while there is evidence that welfare quarantining may be assisting some individuals to stabilise their lives (DSS ; Orima ; Scott et al. ), positive outcomes have typically been seen only among participants in voluntary income management (VIM) programmes, or in instances where “individuals are motivated to make changes, and where they are supported by caseworkers and other interventions” (Bray 2016a:464; see also Bray 2016b).…”
Section: Cim and The Causes Of Homelessnessmentioning
confidence: 99%